Pengalaman Keluarga dalam Merawat Anggota Keluarga dengan Post CVA: Studi Kasus (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2024)
Background: Patients with post CVA have difficulties in carrying out their daily activities because of the limited mobility they experience. These obstacles make them need special attention from their family members. In responding to situations like the above, there are several things that are done by the family, one of which is to seek physiotherapy assistance to reduce the level of immobility of the patient. The purpose of this study was to describe the experiences of families in caring for family members with post CVA. Method: This research method uses a qualitative research method with a case study approach. The selection of participants used a purposive sampling method with three participants. While data collection used semi-structured interviews and documentation, with data triangulation as a test of validity and analyzed using thematic analysis. The data collection tool used was a list of interview questions and a cell phone as a recorder. Results: The results of the study found 4 themes, namely: (1) Family experience in meeting the needs of the elimination pattern, (2) Family experience in fulfilling the family support, (3) Family experience in fulfilling the pattern of nutrition fulfillment, (4) Family experience in meeting the needs of the sleep pattern. Discussion: the efforts of participants as children and husbands who have family members with Post CVA conditions in parenting are quite good. despite facing various difficulties, family members have their own way of dealing with these difficulties, so that Mrs. J has enthusiasm in dealing with the conditions he is experiencing and progressing in his condition or rehabilitation stage.